The Phenomenon of Online Shopping Behavior on the Shopee Application During a Pandemic - Yoga Aprianto; Sri Narti; Vethy Octaviani (Penerbit Jurnal Indonesia, 2022)
During the COVID-19 pandemic, lectures are simultaneously conducted online. Activities carried out at home also vary, ranging from developing hobbies, exercising, and even shopping online. This study aims to determine the phenomenon of online shopping behavior in the pandemic period (Study on the Shopee Application). Data collection techniques in this study used the interview method. Based on the results of this study, the phenomenon of online shopping behavior is the increasing interest in shopping at Shope during the pandemic. The phenomenon of online shopping behavior at Shopee is influenced by several factors, namely cultural, social, personal and psychological factors. The cultural factor in online shopping on the Shopee application is one of the lifestyles and has metamorphosed into popular culture by students of the Communication study program at the University of Dehasen Bengkulu. Social factors are one of the factors that can affect shopping at Shopee. Through this factor, students use shopee because they interact with their social environment. Then personal factors, Communication students at the University of Dehasen Bengkulu use Shopee to meet their needs. And psychological factors, students use Shopee to get satisfaction in shopping.